Explaining the Universlity of Dirac's Idea and Theory (Global Journal of Science Frontier Research, 2020)
The article explains the recently found wide application of the Dirac's theory to a long list of materials. The Dirac theory was initially created only for electrons. The wide applicability is based on the fact that Dirac postulated that dark matter with negative energy and negative mass, called anti-matter, co-exists with the matter, which allowed him to predict the positron. The author of this article is convinced that dark anti-matter with negative energy gives birth of the whole light material world and the whole Universe is a constant dynamic transformation of dark matter (antimatter) into light matter and recycling of disordered light matter into dark anti-mater. During the birth of the material world, the nonlinear electromagnetic field (NEMF), which separates the dark anti-matter from the light matter, gets imprinted on all material creations. The NEMF, which is present in all materials, is what makes the applicability of the Dirac theory so wide.
Keywords: Dirac theory; universal Dirac theory; universal quantum electrodynamics (QED); material bodies and NEMF